2013
DOI: 10.2174/1389202911314020002
|View full text |Cite
|
Sign up to set email alerts
|

MutS Homologues hMSH4 and hMSH5: Genetic Variations, Functions, and Implications in Human Diseases

Abstract: The prominence of the human mismatch repair (MMR) pathway is clearly reflected by the causal link between MMR gene mutations and the occurrence of Lynch syndrome (or HNPCC). The MMR family of proteins also carries out a plethora of diverse cellular functions beyond its primary role in MMR and homologous recombination. In fact, members of the MMR family of proteins are being increasingly recognized as critical mediators between DNA damage repair and cell survival. Thus, a better functional understanding of MMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…Our results demonstrated that in EWS cells trabectedin increases expression of BRCA1, BRCA2, key proteins in the HR pathway as well as of XRCC1, which is involved in the SSR pathway, resulting in DNA damage as indicated by phosphorylation of histone H2AX and accumulation of intranuclear foci. The drug combination with OSI-906 maintains and even increases upregulation of members of HR (RAD52, BRCA1, and BRCA2), NER (XPA and ERCC1), and SSR (XRCC1) pathways but also induces a strong downregulation of XRCC4 and XRCC6 as well as of MSH4 and MSH5, two molecules involved in the maintenance of genomic stability and mitotic DSB repair (52), indicating general alterations of DNAdamage response and repair pathways. This is in line with recent evidence that IGF1R inhibition induces a direct functional defect in DSB repair by both NHEJ and HR, besides indirectly impairing HR through influences on the expression and/or activation of cell- (1) but also enhance the binding of EWS-FLI1 to target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that in EWS cells trabectedin increases expression of BRCA1, BRCA2, key proteins in the HR pathway as well as of XRCC1, which is involved in the SSR pathway, resulting in DNA damage as indicated by phosphorylation of histone H2AX and accumulation of intranuclear foci. The drug combination with OSI-906 maintains and even increases upregulation of members of HR (RAD52, BRCA1, and BRCA2), NER (XPA and ERCC1), and SSR (XRCC1) pathways but also induces a strong downregulation of XRCC4 and XRCC6 as well as of MSH4 and MSH5, two molecules involved in the maintenance of genomic stability and mitotic DSB repair (52), indicating general alterations of DNAdamage response and repair pathways. This is in line with recent evidence that IGF1R inhibition induces a direct functional defect in DSB repair by both NHEJ and HR, besides indirectly impairing HR through influences on the expression and/or activation of cell- (1) but also enhance the binding of EWS-FLI1 to target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have been published on the associations between SNPs in DNA repair genes and the risks of various cancers [5], a study of SNPs in MMR genes in the context of PHC susceptibility has not been reported. This study selected seven loci in MMR genes, including MLH3 (rs175080) [8,9], PMS1 (rs5742933) [10], PMS2 (rs1059060) [11], MSH3 (rs26279) [12], MSH5 (rs1150793, rs2075 789) [12,13] and MSH6 (rs1042821) [14] to investigate the relationship between polymorphisms in MMR genes and the risk of PHC for the Han population in northern China.…”
Section: Introductionmentioning
confidence: 99%
“…The human hMSH5 gene is associated with several coding region non-synonymous polymorphisms [5], [40]; however, the functional significance of these polymorphic variants has not been investigated experimentally. This is an important issue because common genetic variations in DNA damage response and repair genes can affect DNA repair and cancer predisposition [41].…”
Section: Resultsmentioning
confidence: 99%